Delegating Decisions to Experts - Li, Hao; Suen, Wing (Journal of Political Economy, 2004)
We present a model of delegation with self-interested and privately informed experts. A team of experts with extreme but opposite biases is acceptable to a wide range of decision makers with diverse preferences, but the value of expertise from such a team is low. A decision maker wants to appoint experts who are less partisan than he is in order to facilitate information pooling by the expert team. Selective delegation, either by controlling the decision-making process or by conditioning the delegation decision on his own information, is an effective way for the decision maker to safeguard own interests while making use of expert information. © 2004 by The University of Chicago. All rights reserved.